Educational Experiences and Outcomes of Black Youth in Quebec English-Language High Schools - Quebec English-speaking Communities Research Network (QUESCREN) (2024)

Wellness Innovation Lab - Variantzas, Bobbie (QUESCREN Education and Vitality Forum 2023, 2023)

An Independent Report of the History Experts Committee On the Provincial History of Québec and Canada Program and Approved English Textbooks - Commission scolaire English-Montreal / English Montreal School Board (2018)
In September 2017, the Ministry of Education implemented a revised Secondary III and IV compulsory History of Québec and Canada program. This program raised a number of issues that became of concern to the English Montreal School Board (EMSB). Given these concerns, the EMSB commissioned an independent History Experts Committee to review the content of this program as well as the Ministry-approved English-language textbooks. The following is a summary of the findings of this Committee

Secondary School Exchanges : A Promising Way of Fostering Bilingualism in the Next Generation - Lai, Edward; Orme, Charlie; Fleming, Scott (Y4Y Québec, 2018)
In Quebec, it is a basic fact that a solid grasp of the French language is essential to finding work, participating fully in the political process, and integrating into society. While statistics show that bilingualism is very common among the Englishspeaking minority, and especially so among youth, problems nonetheless arise. Young English-speakers frequently report that they do not feel confident enough in their ability to speak French, while others remark that their written French is not strong enough to land a job. Inadequate knowledge of French is a contributing factor to the higher unemployment rates experienced by young English- speakers. A lack of work, and a hampered ability to take part in public life in general, lead to the disenfranchisement of members of this community. Given the high demand among young English- speakers for more French-language training, policy makers must come up with new and creative ways of meeting the demand.

A Brief to the Minister of Education on the Consultation Document "Moving Ahead" from Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1993)
One of the stated aims of the Home and School movement is to assist in forming public opinion favourable to reform and to the advancement of the education of the child. Thus we are pleased to be able to submit this brief to the Minister of Education in response to her consultation document "Moving ahead". The document has been studied with interest by QFHSA's Education Committee. The Minister is to be commended for focusing on concerns that are being currently voiced regarding the education system and for putting forward proposals to address these concerns. However the short time allowed for consultation has meant that QFHSA has been unable to involve the local school associations in drawing up this brief.

A Brief Presented by Quebec Federation of Home and School Associations to the Minister of Education on the Green Paper on Primary and Secondary Education in Quebec - Quebec Federation of Home and School Associations (QFHSA) (1978)
The Quebec Federation of Home and School Associations, now in the 34th year since its inauguration, represents over 11,000 Quebec families, members of local associations, throughout the province. In addition to local associations, many School Committees of the English sector of Quebec education are associate members of Federation The objectives of our Federation, as contained in the Standing Rules, include the following: "To promote progressive legislation for the care, protection and education of children and youth. To work for the continuing advancement of education in this province so that our young people shall be better educated, trained and equipped for life." In fulfilling these objectives, on innumerable occasions Quebec Federation has prepared and submitted briefs, position papers and other statements of policy to successive provincial governments on matters related to education. Our submissions date from before the. creation of the Ministry to the present